تطبيق طريقة التقليد والحفظ لتعلم اللغة العربية في المعهد الإمارة المستقيمة باجولماتي بانيوانجي جاوى الشرقية - Hidayatul Laili Fitriah; Muhamad Alfankarim Romadhoni; Nuril Mufidah; R. Taufiqurrochman (Jurusan Pendidikan Bahasa Arab, 2023)
Abstrak : Arabic is a very important language for millions of Islamic people around the world both Arabic and non-Arab, al- Imaratul Mustaqimah islamic boarding school is one of the islamic boarding schools that creates cadres of Islamic cadres and cadres of the nation by equipping their students with learning Arabic. The existence of phesantren as an uplifting educational institution is increasingly challenged to improve itself in every activity carried out in the book, for example in the practice of teaching methods. Learning methods are one of the important factors in the continuity of learning Arabic. for the success of teaching relating to the methods used . MIM stands for mimicry which means to imitate and memorization which means memorization. the methods used in teaching at Al Imaratul Mustaqimah islamic boarding school are usually very monotonous and even the use of methods is not in accordance with the learning objectives The main problems of this study are: (1)How is the application of the mimicry and memorization method in kalam skills in pesantren (2) how is arabic learning in pesantren? This type of research is an experimental research design with the use of pretest and posttest in one group. the sample of this study was some of the students of Al-Imaratul Mustaqimah Islamic boarding school. The results of this study can be concluded as follows that the method of mimicry and memorization in order to improve the development of speech skills is very effective.